Evaluation of the current methods used for assessing dietary intake in military research settings: a scoping review. Issue 2 (27th August 2020) - Chapman, Shaun; Rawcliffe, A J; Smith, L; Izard, R; Roberts, J
Abstract : Introduction: It is important to collate the literature that has assessed dietary intake within military settings to establish which methods are commonly used and which are valid so that accurate nutrition recommendations can be made. This scoping review aims to identify which methods are typically used to assess dietary intake in military settings and which of these have been validated. This review also aims to provide a recommendation as to which method(s) should be used in military settings. Methods: This scoping review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews. Searches were conducted in PubMed, Web of Science and SPORTDiscus with the most recent search executed on 12th June 2020. Eligible studies had to report original data, assess and quantify dietary intake and have been published in peer-reviewed academic journals. The reporting bias was calculated for each study where possible. Results: Twenty-eight studies used a single method to assess dietary intake and seven studies used a combination of methods. The most commonly used methods were the gold standard food intake/waste method, Food Frequency Questionnaire (FFQ) or a food diary (FD). The only method to date that has been validated in military settings is weighed food records (WFR). Conclusions: The food intake/waste method or WFR should be used where feasible. Where this is not practical the FFQ or FD should be considered with control measures applied. There is currently not sufficient evidence to state that using multiple methods together improves validity.